2021
DOI: 10.1016/j.canlet.2020.12.029
|View full text |Cite
|
Sign up to set email alerts
|

The anti-tumour activity of DNA methylation inhibitor 5-aza-2′-deoxycytidine is enhanced by the common analgesic paracetamol through induction of oxidative stress

Abstract: The DNA demethylating agent 5-aza-2′-deoxycytidine (DAC, decitabine) has anti-cancer therapeutic potential, but its clinical efficacy is hindered by DNA damage-related side effects and its use in solid tumours is debated. Here we describe how paracetamol augments the effects of DAC on cancer cell proliferation and differentiation, without enhancing DNA damage. Firstly, DAC specifically upregulates cyclooxygenase-2-prostaglandin E 2 pathway, inadvertently providing cancer cells with survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, synergistic cytotoxicity and apoptosis were observed when two drugs were applied at the concentration of 5 µM, which is a five-time higher concentration than used in the present study [ 28 ]. Furthermore, 5-azadC, a derivative of 5-azaC, when co-treated with paracetamol, promoted glutathione depletion and ROS accumulation that had an anticancer action against head and neck squamous cell carcinoma and acute myeloid leukemia cell lines [ 29 ]. The sensitizing effect of paracetamol supplementation was not achieved when 5-azaC was co-administered [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, synergistic cytotoxicity and apoptosis were observed when two drugs were applied at the concentration of 5 µM, which is a five-time higher concentration than used in the present study [ 28 ]. Furthermore, 5-azadC, a derivative of 5-azaC, when co-treated with paracetamol, promoted glutathione depletion and ROS accumulation that had an anticancer action against head and neck squamous cell carcinoma and acute myeloid leukemia cell lines [ 29 ]. The sensitizing effect of paracetamol supplementation was not achieved when 5-azaC was co-administered [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 5-azadC, a derivative of 5-azaC, when co-treated with paracetamol, promoted glutathione depletion and ROS accumulation that had an anticancer action against head and neck squamous cell carcinoma and acute myeloid leukemia cell lines [ 29 ]. The sensitizing effect of paracetamol supplementation was not achieved when 5-azaC was co-administered [ 29 ]. Thus, oxidative stress-mediated anticancer action of combined treatment is specific to 5-azadC [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 One of the consequences of the degrading intracellular level of GSH is the enhancement of oxidative stress, which is beneficial to cancer therapy. 15,16 To achieve intracellular oxidative stress, there have been two strategies: elevating the level of ROS and depleting antioxidants such as intracellular GSH to realize the goal of elevating the ROS level in cells. 17,18 Recently, considerable attention has been given to a novel strategy of a cascade reaction for tumor treatment in which GSH was depleted to elevate the ROS level on one hand, and on the other hand, the ROS level was raised by simultaneously undergoing a Fenton or Fenton-like reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are mainly three electrochemical equilibria to achieve intracellular redox balance: (i) coenzyme II system: NADPH/NADP + ; (ii) glutathione system: GSH/GSSG; (iii) thioredoxin system: Trx­(SH) 2 /TrxSS. Among these three redox couples, the pair GSH/GSSG plays the most important role, and the concentration level is much higher than those of the other two by >100-fold, which chiefly dictates intracellular redox status. , It has been widely reported that decreases in the expression of GSH would trigger programmed cell death in several pathways, for example, apoptosis, , ferroptosis, , necroptosis, and autophagy. , In these cases, cell deaths mainly contributed to the elevated levels of reactive oxygen species (ROS) induced by GSH depletion . One of the consequences of the degrading intracellular level of GSH is the enhancement of oxidative stress, which is beneficial to cancer therapy. , To achieve intracellular oxidative stress, there have been two strategies: elevating the level of ROS and depleting antioxidants such as intracellular GSH to realize the goal of elevating the ROS level in cells. , …”
Section: Introductionmentioning
confidence: 99%